2021
DOI: 10.1111/jvim.16137
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of transdermal gabapentin in cats

Abstract: Background: Clinical use of gabapentin has increased; transdermal delivery in cats is incompletely studied.Objective: To evaluate if gabapentin permeates feline skin in vitro and in vivo and to determine if pain scores improve after administration. Animals: In vitro: cadaver skin from 6 cats; phase 1: 8 young, healthy client-owned cats; phase 2: 15 client-owned geriatric cats.Methods: In vitro, gabapentin applied every q12h to ear or cervical skin in diffusion cells. Samples collected at 0, 2, 4, 12, and 24 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the study by Adrian et al (2018) [95], the transdermal formulation was also explored, but the drug concentrations were too low to be modelled with appropriate pharmacokinetic analysis, probably because of the poor absorption of the gabapentin preparation used [95]. Conversely, the results from the most recent study regarding transdermal gabapentin use in cats appeared to be promising and encouraged further investigations on the use of this alternative administration route [78]. Indeed, the results provided by Slovak and Costa (2021) [78], using gabapentin in a 10% or 20% Lipoderm base transdermal preparation, clearly demonstrated that this drug can permeate feline skin in vitro and can be systemically absorbed in vivo, advocating the need to deepen the knowledge on this administration route [78].…”
Section: Pharmacokinetics In Catsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Adrian et al (2018) [95], the transdermal formulation was also explored, but the drug concentrations were too low to be modelled with appropriate pharmacokinetic analysis, probably because of the poor absorption of the gabapentin preparation used [95]. Conversely, the results from the most recent study regarding transdermal gabapentin use in cats appeared to be promising and encouraged further investigations on the use of this alternative administration route [78]. Indeed, the results provided by Slovak and Costa (2021) [78], using gabapentin in a 10% or 20% Lipoderm base transdermal preparation, clearly demonstrated that this drug can permeate feline skin in vitro and can be systemically absorbed in vivo, advocating the need to deepen the knowledge on this administration route [78].…”
Section: Pharmacokinetics In Catsmentioning
confidence: 99%
“…For the control of chronic osteoarthritis-related pain, gabapentin was associated with improvement in owner-identified impaired activities, but with a lack of improvement in the owners’ reported quality of life, probably due to the high incidence of sedative effects [ 40 , 78 ]. In a preliminary study on transdermal administration of gabapentin in geriatric cats, drug systemic absorption and a decrease in pain scores were observed [ 78 ]. Conversely, gabapentin administered at three different doses did not affect the thermal threshold in healthy cats and, therefore, was not able to provide thermal antinociception [ 79 ].…”
Section: Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…161 However, another study showed that gabapentin in the proprietary base Lipoderm did result in measurable plasma concentrations. 163 The authors of the latter study caution that their investigation involved a small number of cats and, because grooming was allowed, uptake may have occurred transmucosally. More studies using different transdermal creams, concentrations, doses and dosing intervals are needed.…”
Section: Adjuvant Analgesic Drugsmentioning
confidence: 99%